The development and validation of the COVID-19 Depression Scale (COVID-19DS): association with the Perceived Health-Related Components Scale - Dadfar, Mahboubeh (Mental health, religion & culture, 2023)
The aims of the study were: (a) to develop, assess the psychometric properties and explore the factorial structure of the COVID-19 Depression Scale (COVID-19DS), (b) to explore correlations of the COVID-19DS scores with the Perceived Health-related Components Scale (PHCS) scores, and (c) to examine gender differences. A total sample of 313 Turkish students was selected. Cronbach's α was .92. Two factors were extracted and labeled Affective, Cognitive, and Somatic/Vegetative and COVID-19 Depression. The COVID-19DS score was negatively correlated with the PHCS score. Females scored higher than males on the COVID-19DS, and lower than males on the PHCS. Perceived health-related components were most frequently rated as much worse or worse for current status compared to before the COVID-19 outbreak. The COVID-19DS is recommended for use in assessing depression due to coronavirus and as a screening tool to identify those with extremely high scores who may be in need of psycho-educational interventions.